Bad Faith: Inequality and discrimination within UK healthcare regulation (Existential Analysis: Journal of the Society for Existential Analysis, 2021)
The methods operated by UK healthcare regulators when investigating claims of practitioner wrongdoing exhibit judicial irregularities and morally questionable methods. Highlighting how and where regulators fail to execute their fitness-to-practice mandates ethically provides an opportunity for fairer and safer systems of regulatory oversight to be contemplated. Taking into consideration concepts of bad faith, this paper is an analysis of how the regulatory establishment administers fitness-to-practice procedures, and seeks to illustrate how existing approaches harm the credibility and efficacy of healthcare regulation.
Keywords: Bad faith; regulation; fitness-to-practice; ethics; judicial irregularity; discrimination